O fazer quadrinístico em Dom Casmurro: uma análise entre as adaptações de Wellington Srbek, José Aguiar (2011) e Alex Mir e Caio Majado (2019) com a obra adaptada - CRUZ, Amanda Gomes (2026)
Comic books are recognized as a cultural manifestation that has gained prominence over time, becoming an important medium for the adaptation of literary works. When dealing with such adaptations, it is necessary to consider not only the transposition from one textual genre to another, but also the change in language, contexts of production, and authorship, factors that make certain modifications inevitable. In light of this, this study carries out a comparative analysis of two comic book adaptations of Dom Casmurro: the first, produced by Wellington Srbek and José Aguiar (2011), and the second, by Alex Mir and Caio Majado (2019). Throughout the analysis, the aim was to understand how the comic making process occurred, that is, the process of transforming literary texts into comics, by investigating how the original text was transposed into graphic narrative form. More specifically, the study sought to examine the aesthetic and narrative choices present in the comic book adaptations of Dom Casmurro, to investigate how multimodal language is constructed in comics in contrast to the exclusively verbal language of the original work, to analyze how central elements of the narrative were re- signified in the transition from the literary text to the graphic medium, and to compare the adaptations by Wellington Srbek and José Aguiar (2011) and by Alex Mir and Caio Majado (2019), identifying the particularities of each approach and their implications for the re-creation of Machado de Assis’s work. To this end, the theoretical framework draws on the propositions of Hutcheon (2013), Stam (2000), and Camello (2017) regarding adaptation theory, as well as those of Eisner (1995), McCloud (2008), and Ramos (2009) with respect to comic books. The methodology adopted, of a descriptive exploratory nature, was based on a selective review of bibliographic data and on the application of the comparative method, through the analysis of selected scenes from the original work and its two comic book adaptations. Initially, these scenes were compared with the source text and, subsequently, the adaptations were compared with one another, which allows the conclusion that, despite their different approaches, both aim to make the classic accessible to new audiences while preserving the prestige of Machado de Assis’s work, albeit through distinct paths: the first through an interpretative re-creation, with greater graphic expressiveness and a focus on narrative point of view, and the second through a more literal reading, centered on the literary text.